Development of seismic fragility curves for buckling- restrained braced structures under far-field motions considering soil-structure interaction - Hasan Ghasemzadeh; Reza Khodabakhshi Soureshjani (Results in Engineering)
The traditional design criterion for buckling restrained braces (BRB) is established based on the fixed base model, which is appropriate for situations where significant soil-structure interaction (SSI) effects are absent. This paper presents a study considering the SSI effect of the 4, 6, and 8-story BRB structures with split X and Chevron V invert configurations. The study includes fragility seismic analysis, considering the SSI effects on BRB structures at different performance levels, such as immediate occupancy (IO), life safety (LS), and collapse prevention (CP). The nonlinear soil behavior is represented using the Drucker-Prager model, and the soil boundary conditions are determined based on the Leismer theory. The BRB structures are subjected to incremental dynamic analysis (IDA) using 22 far-field ground motions from FEMA P695 to create seismic fragility curves. The study findings indicate a significant rise in axial deformation of BRBs at various performance levels when the SSI effect is present. The increase in axial deformation of BRB has caused earlier damage and failure of this structure. Therefore, it is highly advisable to consider the SSI effects in the analysis and design of buckling restrained braced (BRB) structures with six stories or fewer to ensure the desired structural response during seismic events.